2014
DOI: 10.1039/c4py00040d
|View full text |Cite
|
Sign up to set email alerts
|

pH-responsive layer-by-layer films of zwitterionic block copolymer micelles

Abstract: We report a strategy to incorporate micelles of poly[3-dimethyl (methacryloyloxyethyl) ammonium propane sulfonate]-block-poly[2-(diisopropylamino)ethyl methacrylate] (bPDMA-b-PDPA) into electrostatic layer-by-layer (LbL) films. We obtained micelles with pH-responsive PDPA-cores and zwitterionic bPDMA-coronae at pH 8.5 through pH-induced self-assembly of bPDMA-b-PDPA in aqueous solution. To incorporate bPDMA-b-PDPA micelles into LbL films, we first obtained a net electrical charge on bPDMA-coronae. Negative cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…In addition, owing to their hydrophobic micellar cores, BCMs increase the loading capacity of LbL films for drug molecules with low water solubility. Multilayers containing stimuli‐responsive BCMs have been reported earlier . In this study, we report on preparation of LbL films containing PDMA‐ b ‐PDEA micelles and the effect of film deposition pH and temperature on the properties of the micellar multilayers.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, owing to their hydrophobic micellar cores, BCMs increase the loading capacity of LbL films for drug molecules with low water solubility. Multilayers containing stimuli‐responsive BCMs have been reported earlier . In this study, we report on preparation of LbL films containing PDMA‐ b ‐PDEA micelles and the effect of film deposition pH and temperature on the properties of the micellar multilayers.…”
Section: Introductionmentioning
confidence: 86%
“…Multilayers containing stimuli-responsive BCMs have been reported earlier. [24][25][26][27][28][29][30][31][32][33][34] In this study, we report on preparation of LbL films containing PDMA-b-PDEA micelles and the effect of film deposition pH and temperature on the properties of the micellar multilayers. We found that only 0.5 unit difference in film deposition pH or 5 °C difference in film deposition temperature can lead to multilayer films with drastically different pH-stability and release properties from surface.…”
mentioning
confidence: 99%
“…The related aggregate structures can reversibly dissolve, swell or shrink depending on the pH of the medium (Figure 4d) [27][28][29][30][31]. When these polymers are used in various surface applications such as films, layerby-layer (LbL) technology, membranes, brushes, many behaviors such as ion selective permeability, surface charge change, wettability, change in pore size and thickening/thinning of the polymer layer are encountered [32][33][34][35][36][37][38][39]. When these polymers are involved in surface applications such as membranes, numerous behaviors such as ion selective permeation and change in pore size are encountered (Figure 4f) [39][40][41][42].…”
Section: Ph-responsive Polymersmentioning
confidence: 99%
“…LbL assembly of microgel [ 56 ] or micellar [ 57 ] structures has also been demonstrated in the literature as a method to control responsive properties of the material. By varying the composition of the microgels, Clark and Lyon showed that the temperature response of the LbL-assembled film of P(NIPAAm- co-N -isopropyl methacrylamide) microgels with a polycationic layer could be tuned not only by the composition of the microgels, but also by the ratio of different microgel compositions assembled in the film [ 56 ].…”
Section: Layer-by-layer Assemblymentioning
confidence: 99%
“…Similarly, Yusan et al [ 57 ] found that the upper critical solution temperature (UCST) response of the zwitterionic poly[3-dimethyl (methacryloyloxyethyl) ammonium propane sulfonate] (β-PDMA)-coronae of micelles assembled via LbL deposition into a multilayer film altered the effect of decreasing pH on the film thickness. The increase in thickness of the film at a temperature below the UCST was attributed to the phase separation of the β-PDMA chains, resulting in voids within the multilayers that increased the imbibition of water and volume of the film.…”
Section: Layer-by-layer Assemblymentioning
confidence: 99%